2022
DOI: 10.1177/14644207221139182
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of an alternative approach to temporarily repair Nomex honeycomb sandwich structures in aerospace applications

Abstract: In this study, the effectiveness of an alternative approach to temporarily repair an open-hole damaged Nomex honeycomb sandwich structure is experimentally investigated. The repair process consists of a resin-infused carbon fabric wet layup patch adhesively bonded to the facesheets and Airex structural foam used as a core replacement plug. The specimens of intact, damaged and repaired Nomex honeycomb sandwich panels are subjected to the quasi-static three-point bending test. The panel's flexural performances a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Extensive research has been carried out along the utilization of Nomex honeycomb in an aerospace application, diverging to the equation about how it behaves in the crash scenario and crush force efficiency [12]. Khaire et al [13] investigating hemispherical aluminium sandwich shell structures found that thicker face-sheets enhance ballistic performance through mechanisms like ductile tearing and petal formation.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has been carried out along the utilization of Nomex honeycomb in an aerospace application, diverging to the equation about how it behaves in the crash scenario and crush force efficiency [12]. Khaire et al [13] investigating hemispherical aluminium sandwich shell structures found that thicker face-sheets enhance ballistic performance through mechanisms like ductile tearing and petal formation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the repair filling material may be the same parent core material 16 but also a neat resin, a resin mixed with chopped fibers, 9 or other materials similar to the parent one. 23 In this study, the influence of the core plug replacement parameters on the flexural performances of the repaired composite honeycomb sandwich panel was investigated. Numerical analyses of the three-point bending test are conducted using the non-linear finite element (FE) code Abaqus/Explicit.…”
Section: Introductionmentioning
confidence: 99%